The Impact of the COVID-19 Pandemic on the Production and Price of Poultry Products in Romania - Elena Adriana Sima (Marin); Dorina Nicoleta Mocuta (Journal of Agriculture and Rural Development Studies, 2025)
Poultry products (eggs and meat) are some of the basic agri-food products globally, being part of over 85% of the population’s diet. This study follows the evolution of the logistics of poultry products, generated by the imposition of the state of emergency and home isolation. Based on Romanian National Institute of Statistics data, it can be established how production fluctuated in the years 2020-2023, compared to the pre-pandemic period, as well as how the prices of eggs and chicken meat have changed in the same period. The correlation between these two parameters leads to interesting conclusions regarding the impact generated by the Covid-19 pandemic on consumer preferences. Part of the increase in the number of birds since 2021 is due to the migration trend of the population from urban to rural areas, where many people decide to produce part of their own food. It can be concluded that any major disruption will lead to imbalances related to production and price levels, but these will be regulated in a short period of time, through measures taken at a general level (state support) or individually.